Effect of substitution and temperature on the corrosion inhibition properties of benzimidazole bearing 1, 3, 4-oxadiazoles for mild steel in sulphuric acid: Physicochemical and theoretical studies. Issue 1 (February 2018) - Rugmini Ammal, P.; Prajila, M.; Joseph, Abraham
Highlights: MBIMOT, EBIMOT and PBIMOT act as efficient inhibitors for mild steel corrosion in 0.5 M H2 SO4 . The IE has a direct relation with inhibitor concentration and an inverse relation with temperature. The mechanism of inhibition is by adsorption which follows Langmuir isotherm. The theoretical and experimental correlation is very good with very few exceptions. Abstract: Three 1, 3, 4-oxadiazole derivatives viz 5-((2-methl-1H-benzo[d]imidazol-1-yl) methyl)-1, 3, 4-oxadiazole-2-thiol (MBIMOT), 5-((2-ethyl-1H-benzo[d]imidazol-1-yl) methyl)-1, 3, 4-oxadiazole-2-thiol (EBIMOT) and 5-((2-propyl-1H-benzo[d]imidazol-1-yl) methyl)-1, 3, 4-oxadiazole-2-thiol (PBIMOT) were synthesized and their corrosion inhibition ability towards mild steel in sulphuric acid has been assessed by gravimetric, electrochemical, SEM and computational methods and using thermodynamic and kinetic parameters. The charge transfer resistance increases when inhibitor concentration does, based on EIS, indicates protective layer formation and is substantiated by SEM micrographs, whereas polarization studies revealed the mixed type behaviour of these inhibitors. The adsorption characteristics described by Langmuir adsorption isotherm along with thermodynamic and kinetic parameters suggested a mixed physisorption and chemisorptions of inhibitors on mild steel surface.